Wacław Potocki i Podgórze Karpackie - peryferyjne centrum teologicznej refleksji poety („Tydzień stworzenia świata” - „Ogród”) - Obremski, Krzysztof (Studia Europaea Gnesnensia, 2010)
Each period possesses its own concept of world and man. The article presents the attitude of a man of Baroque to the surrounding reality, on the example of Wacław Potocki’s work. The author indicates the Biblical mediation of anthropological and existential threads, which endows Potocki’s poetry with a universal dimension.